The Effectiveness of Dialectical Behavioral Therapy on Stress and Cognitive Flexibility in Women With Type 2 Diabetes - Fatemeh Khakshoor Shandiz (Qom University of Medical Sciences, 2021)
Background and Objectives: Diabetes has irreversible effects on the physical and mental functioning of people with diabetes, therefore performing psychological interventions for patients with diabetes seems necessary. Accordingly, the present study aimed to determine the effectiveness of dialectical behavioral therapy on stress and cognitive flexibility of women with type 2 diabetes. Methods: The present study was a quasi-experimental one with pre-test and post-test design and with a control group. Among the statistical population, which included all women with diabetes referred to the Diabetes Center of Birjand in the second 6 months of 2018, 30 people were selected by convenience sampling method and randomly divided into experimental and control groups. The dialectical behavior therapy program was performed for the experimental group in eight 60-minute sessions weekly. Data were collected by Stress Questionnaire (Lovibond & Lovibond, 1995) and Cognitive Flexibility Questionnaire (Dennis & Wendrew, 2010) before and after the intervention, and were analyzed using univariate and multivariate analysis of covariance in the environment of SPSS v. 24 at a significance level of 0.05. Results: The results showed that in the post-test stage there was a significant difference between mean scores of stress and cognitive flexibility in experimental and control groups; in other words, dialectical behavior therapy significantly increased cognitive flexibility and reduced stress in patients with type 2 diabetes (P<0.01). Conclusion: Based on the obtained results, in the therapeutic interventions of diabetic patients using effective treatment methods such as dialectical behavior therapy, it is necessary to pay more attention to the improvement of their psychological conditions.